Effects of Short or Long-Term Exposure of Dithiopyr on Certaine Blood, Growth and Tissue Biochemical Parameters in Catfish (Clarias garipinus) - Attia, Kamal A.; El-Badawi, Ashraf A. (International Journal of Applied Sciences and Biotechnology, 2015)
In the current study the effects of acute or chronic exposure of dithiopyr herbicide (weed controllers) in Catfish (Clarias garipinus) was studied. LC50 was determined, and recorded as 460 μgl-1. Acute and chronic effects on certain blood, growth and tissue biochemical parameters were studied as a function of exposure time. Exposure of Clarias garipinus to acute or chronic toxicity of the herbicide resulted in significant increase in glucose, total cholesterol, creatinine, uric acid and Lactate dehydrogenase (LDH) in the herbicide-treated group, while aspartate aminotransferase (AST) and alanine aminotransferase (ALT) showed a fluctuating activities in both exposures. In contrast, there was significantly (P<0.01) lower values for liver and muscle glycogen in acute toxicity as compared with the control group. Also, in herbicide exposed fish a significant reduction in growth parameters was recorded. These alterations could be attributed to the changes in the metabolic pathways of the studied fish that meight be takes place as a secondary response in the fish to provide energy for the "fight-or-flight" reaction and to compensate the high energy demand. This study implies the importance of previous knowledge about the susceptibility of cultured fish species before using herbicides. Int J Appl Sci Biotechnol, Vol 3(2): 314-321 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12686